2011
DOI: 10.1089/ten.tea.2007.0244
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Electrical Field Stimulation Aids in Tissue Engineering of Multicell-Type Cardiac Organoids

Abstract: The main objectives of current work were (1) to compare the effects of monophasic or biphasic electrical field stimulation on structure and function of engineered cardiac organoids based on enriched cardiomyocytes (CM) and (2) to determine if electrical field stimulation will enhance electrical excitability of cardiac organoids based on multiple cell types. Organoids resembling cardiac myofibers were cultivated in Matrigel-coated microchannels fabricated of poly(ethylene glycol)-diacrylate. We found that field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 27 publications
8
93
1
1
Order By: Relevance
“…The maximum capture rates for the cardiac tissues were similar with or without vascular structures (Fig. 6C) and were comparable to values from our previous studies (46). Troponin T staining demonstrated that cardiomyocytes grown on vascular structures contained betterorganized sarcomeres than those grown on hydrogel coating only (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The maximum capture rates for the cardiac tissues were similar with or without vascular structures (Fig. 6C) and were comparable to values from our previous studies (46). Troponin T staining demonstrated that cardiomyocytes grown on vascular structures contained betterorganized sarcomeres than those grown on hydrogel coating only (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The phenotype of cardiomyocytes in this system could be enhanced further in future studies by applying electrical (46,47) or mechanical (48) stimulation. EC cords previously led to synchronized contraction of cardiomyocytes and increased Connexin-43 expression because of the improved survival and spreading of cardiomyocytes (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Chui et al showed that when symmetrically square biphasic (positive and negative) electrical signals (2.5 V, 1 Hz, 1 msec duration) were applied to cardiomyocyte-seeded polyethylene glycol constructs in vitro, cell elongation was increased. 41 Moreover, in the same study, a higher cell density was observed, along with the presence of cross-striation, and expression of Connexin 43 (a gap junction protein that propagates electrical signaling in cardiac muscle) was increased. Our results suggest that a nonsymmetrical biphasic electrical signal can also be used to augment multinucleated myotube formation from skeletal myoblasts rather than the more common use of symmetrical biphasic (positive and negative) or uniphase pulse signals.…”
mentioning
confidence: 69%
“…The regulatory effect of EFs has been demonstrated on different cell types such as neurons, osteoblasts, myoblasts, fibroblasts, endothelial cells, muscle cell and epithelial cells [8][9][10][11][12][13][14]. These effects result from manipulation of the native EF in the ionic extracellular environment and across the cell membrane [15 -17].…”
Section: Introductionmentioning
confidence: 99%